Pelatihan Aplikasi Microsoft Word, Microsoft Excel dan Power Point Pada siswa-siswi di SMPN 4 Kutacane - Ameliani Rahma Sartika; Elfahmi Lubis; Septina Lisdayanti; Romadhona Kusuma Yudha (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Campus Teaching Activities 3 is a service activity for the world of education. Campus Teaching 3 program in 2022 focuses on literacy, numeracy, administration and technology adaptation of students carried out in isolated, impacted and disadvantaged schools. The purpose of the Teaching Campus activity is (1) Knowing the factors causing the low reading interest of students at school (2) Improving the literacy and numeracy culture in schools (3) assisting school administration (4) students have a responsibility to assist learning activities and help familiarize themselves with technology. The type of research is qualitative with case study method. The subjects adopted in this study were all students of SMP Negeri 4 Kutacane, Mbarung, Babussalam District, Southeast Aceh Regency, Aceh Province due to the students' low understanding of Microsoft Word, Microsoft Excel and Power Point applications. Data collection techniques used in this study were observation, interviews and documentation. The results of the research are (1) Can find out the cause of the students' low understanding of Microsoft Word, Microsoft Excel and Power Point applications, circumstances factors, interest and willingness factors, family environmental factors and school environmental factors. (2) Improving students' understanding of Microsoft Word, Microsoft Excel and Power Point applications with technology adaptation activities at SMP Negeri 4 Kutacane, Mbarung, Babussalam District, Southeast Aceh District, Aceh Province.